2014
DOI: 10.1037/bne0000003
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil reverses nicotine withdrawal-induced deficits in contextual fear conditioning in c57bl/6j mice.

Abstract: Withdrawal from chronic nicotine is associated with cognitive deficits. Therapies that ameliorate cognitive deficits during withdrawal aid in preventing relapse during quit attempts. Withdrawal-induced deficits in contextual learning are associated with nicotinic acetylcholine receptor (nAChR) upregulation. The aim of the present study was to determine if the acetylcholinesterase (AChE) inhibitor donepezil has the ability to reverse nicotine withdrawal-induced deficits in contextual learning. The results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Acute nicotine treatment reverses the impairment produced by nicotine withdrawal on contextual fear conditioning (Davis et al, 2005), as do other putative or current nicotine cessation treatments, including bupropion (Portugal and Gould, 2007), varenicline (Raybuck et al, 2008), donepezil (Poole et al, 2014) and galantamine (Wilkinson and Gould, 2011). The deficits in contextual fear conditioning in these studies has been compared to cognitive deficits in ADHD and are reversed by atomoxetine (Davis and Gould, 2007a).…”
Section: Animal Models Of Nicotine Dependence: Withdrawal Effects On mentioning
confidence: 97%
“…Acute nicotine treatment reverses the impairment produced by nicotine withdrawal on contextual fear conditioning (Davis et al, 2005), as do other putative or current nicotine cessation treatments, including bupropion (Portugal and Gould, 2007), varenicline (Raybuck et al, 2008), donepezil (Poole et al, 2014) and galantamine (Wilkinson and Gould, 2011). The deficits in contextual fear conditioning in these studies has been compared to cognitive deficits in ADHD and are reversed by atomoxetine (Davis and Gould, 2007a).…”
Section: Animal Models Of Nicotine Dependence: Withdrawal Effects On mentioning
confidence: 97%
“…Enhanced cognitive performance following acute nicotine exposure has also been seen in rodent models of attention (Hahn et al 2002). Conversely, nicotine withdrawal produces impairments in both contextual learning and attention-based models (Semenova et al 2007;Gould et al 2012;Portugal et al 2012;Poole et al 2014;Yildirim et al 2015). From these studies, it is apparent that nicotine alters cognitive function in adults depending on multiple factors including duration of treatment.…”
Section: Nicotinementioning
confidence: 98%
“…Decreased contextual fear responses were seen in mice during spontaneous or precipitated nicotine withdrawal, and this reduction during nicotine withdrawal was not seen in mice lacking the β2 nAChR subunit (Portugal et al, ). Nicotine withdrawal effects are also reversed with the α4β2‐selective partial agonists ABT‐089 and varenicline as well as acetylcholinesterase inhibitors such as donepezil and galantamine (Raybuck et al, ; Wilkinson and Gould, ; Poole et al, ; Yildirim et al, ). Much higher doses of donepezil or galantamine were required to enhance conditioned fear responses in nondependent animals, and these effects were associated with enhanced acquisition of conditioned responses and/or unconditioned freezing (Wilkinson and Gould, ; Poole et al, ).…”
Section: Cholinergic Regulation Of Contextual Fear Responsesmentioning
confidence: 99%
“…Nicotine withdrawal effects are also reversed with the α4β2‐selective partial agonists ABT‐089 and varenicline as well as acetylcholinesterase inhibitors such as donepezil and galantamine (Raybuck et al, ; Wilkinson and Gould, ; Poole et al, ; Yildirim et al, ). Much higher doses of donepezil or galantamine were required to enhance conditioned fear responses in nondependent animals, and these effects were associated with enhanced acquisition of conditioned responses and/or unconditioned freezing (Wilkinson and Gould, ; Poole et al, ). Thus, although nicotine can modify contextual fear responses, only a few studies have shown effects of nAChR antagonists or acetylcholinesterase inhibitors (see Table ).…”
Section: Cholinergic Regulation Of Contextual Fear Responsesmentioning
confidence: 99%